The Impact of Social Media and The Presence of Fans at A Sports Event to Attract Private Sector Sponsors (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
The purpose of the present study was to investigate the impact of social media and the presence of fans at a sporting event to attract private sector sponsors. In the present study, in order to investigate the impact of social media and the presence of fans on a sports event in attracting private sector sponsors, the role of new media on how sports sponsors interact and the presence of spectators at sporting events is influenced by the extent to which sponsors participate in events. A review of research on sports media has been used since 2007, given that the category of new media is a new concept in sponsorship. This research seeks to achieve such results by reviewing the research conducted over that timeframe. Sponsorship appeared initially during the early 70s in England in sports and other industries. It subsequently developed in Western countries in the early 90s, experiencing a real boom. Thus, a new term has emerged: sponsorship (sponsorship in French) Indeed to define the word sponsorship (sponsorship and sponsorship will be used as a single term), it is therefore necessary to study precisely the work. It defines sponsorship as a financial investment or materials on an activity, person, or event and having access to a potential communication associated with this activity, person, or event. As a result, Minwan said, the greater the audience participation and the presence of sports media in a sporting event, the greater the attraction of private sponsorship in Moore